Pentoxyphylline: possibilities to reduce manifestations of chronic heart failure with preserved left ventricular ejection fraction in elderly - Shatylo, V. B.; Bodretska, L. A.; Shapovalenko, I. S.; Voinarovska, H. P.; Butynets, Zh. S. (Zaporozhye Medical Journal, 2021)
The aim: to study the effect of add-on pentoxifylline therapy on the structural and functional indicators of the heart state, endothelial function, quality of life and physical abilities in patients with chronic heart failure with preserved left ventricular ejection fraction. Materials and methods. The indicators of the structural and functional state of the heart, endothelial function, quality of life and physical abilities of patients older than 60 years, who were followed-up in the Department of Cardiology of the State Institution “D. F. Chebotarev Institute of Gerontology of the NAMS of Ukraine”, based on 67 case histories, 37 of them were prescribed pentoxifylline as add-on therapy to the standard therapeutic regimen. Statistical data were calculated using modern application packages, in particular SPSS v.22, Statistica 7.0, MedCalc statical software v.11.5.0.0. The significance level was assessed using paired and unpaired Student’s t-test with Bonferroni corrections, and the correlation and two-way analysis of variance were performed. Results. A significant additional effect of pentoxifylline treatment on the indicators of maximum blood flow in the forearm microvessels in response to the reactive hyperemia test, which characterizes the ability of the microvessel endothelium to synthesize relaxation factors, was detected. Patients who additionally received pentoxifylline showed significantly better indicators of left ventricular myocardial relaxation and reduction of hypertrophy than those on the standard therapy. There was a significant increase in walking distance in the third year of treatment in the patients who additionally received pentoxifylline. There was no difference in the impact on the quality of life of the patients. Conclusions. The addition of pentoxifylline to the standard therapy in patients with chronic heart failure with preserved left ventricular ejection fraction significantly reduces myocardial hypertrophy, improves diastolic relaxation, increases volumetric blood flow velocity in microvessels mediating reactive hyperemia, which may contribute to further stabilizing the clinical course of the disease and increasing 6-minute walking distance. The presented data are an additional evidence of pathogenetically reasonable therapy with pentoxifylline in patients with chronic heart failure with preserved left ventricular ejection fraction, which allows us to consider this drug as potentially promising for the routine treatment of such patients.